Testing public health ethics: why the CDC's HIV screening recommendations may violate the least infringement principle. - Pierce, Matthew W; Maman, Suzanne; Groves, Allison K; King, Elizabeth J; Wyckoff, Sarah C (The Journal of law, medicine & ethics : a journal of the American Society of Law, Medicine & Ethics, 2011)
The CDC's HIV screening recommendations for health care settings advocate abandoning two important autonomy protections: (1) pretest counseling and (2) the requirement that providers obtain affirmative agreement from patients prior to testing. The recommendations may violate the least infringement principle because there is insufficient evidence to conclude that abandoning pretest counseling or affirmative agreement requirements will further the CDC's stated public health goals.
Keywords: AIDS Serodiagnosis; Centers for Disease Control and Prevention (U.S.); Counseling; Female; Humans; Informed Consent; Patient Acceptance of Health Care; Patient Rights; Personal Autonomy; Pregnancy; United States